Inhibitions of the Novum - Gabriele Boselli (University of Bologna, 2020)
Despite the increasing number of researchers, the big amount of fundings and the power of A.I. data processing in every field of knowledge, it's about one century that really crucial evolutions don't occur, neither in natural nor in spiritual sciences, somehow comparable to other historical periods, as for example the first thirty years of the last century. The basic sciences, preserved within prestigious disciplinary fences, restricted in their field and stiffened in their form, ignoring the reality as a whole, are inhibited in their most transformative advances. Some of the possible political, economical, linguistic, academic and institutional reasons of this inhibition of the novum are discussed below, hoping to see soon the onset of a truly new paradigm of knowledge.